Therapy with Factor IX Concentrate Resulting in D.I.C. and Thromboembolic Phenomena - Campbell, E.W., Jr.; Neff, Sandra; Bowdler, A.J. (Thrombosis and Haemostasis, 1977)
The development of subclinical D.I.C. in a factor IX hemophiliac receiving concentrate replacement therapy during surgery is discussed with respect to pertinent laboratory features. The case is unique in that factor IX levels were followed carefully and corresponded inversely to the intensity of the D.I.C. Of additional significance is the failure of heparin failure given in conjunction with factor IX concentrate to prevent D.I.C. The value of adequate laboratory monitoring during factor IX replacement therapy is apparent.